In Vitro Anti-Diabetic Potential Extract Test of Seri (Muntingia Calabura, L.) Leaves - Gurning, Kasta; Sinaga, Hilda (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The purpose of this study was to determine the potential of the ethanol extract of the of Muntingia calabura, L (M. calabura) leaves as an anti-diabetic tested by in-vitro using the α-glucosidase enzyme. Methods: extraction by maceration, phytochemical screening using standard testing and testing for anti-diabetic potential were carried out in vitro with observations of inhibition % of the α-glucosidase enzyme from various concentrations of ethanol extract of M calabura (60, 120, 200 and 300 ppm) leaves and acarbose as a standard of comparison. Results: Phytochemical screening showed the ethanol extract content of M. calabura leaves, namely alkaloids, flavonoids, tannins, saponins, triterpenoids and steroids. The ethanol extract of M. calabura leaves has potential as an anti-diabetic and the increase in concentration is directly proportional to its potential activity. Conclusions: The ethanol extract of M. calabura leaves has various types of secondary metabolites such as alkaloids, flavonoids, triterpenoids and steroids, saponins and tannins and has potential as anti-diabetic.